A multi-level random key cryptosystem based on DNA encoding and state-changing mealy machine - Taj, Towshik Anam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2023.